Human factors considerations when developing eHealth solutions to support patients: comparison of Danish and Australian experiences. (1st January 2014) - Roehrer, Erin; Bjørnes, Charlotte D.; Cummings, Elizabeth; Nøhr, Christian
Single snapshot evaluations of eHealth projects often lack depth when explaining the impact of human factor influences at the conceptualisation stages of a project. This paper explores the conceptualisation and prototype building of two eHealth projects undertaken in Denmark and Australia and develops a human factors evaluation framework applicable for use during the initial phases of eHealth projects for patient use. Initially the projects were reviewed using a human factors lens to identify individual project phases. Project elements in each project were determined and analysed using thematic analysis. A conceptual framework was then developed and applied to the project phases resulting in the identification and exploration of five key themes. The developed framework can complement existing eHealth evaluation frameworks and enrich them with a human factors viewpoint and highlights the need for further research on cultural influences and the intersections between each framework component. Finally, the paper highlights the need for patients to be considered as end users of eHealth systems and engaged early and throughout the development of eHealth systems.